Thyroid disfunction and obesity - what comes first? A complex relationship between hypothyroidism and weight gain - Gajdzińska, Natalia; Salwa, Adam; Rostkowska, Weronika; Rutkowski, Wojciech; Sztuba, Karolina; Rzepka, Maciej; Basiura, Karolina; Rymaszewska, Katarzyna; Puchała, Justyna; Starzomska, Dominika (Journal of Education, Health and Sport, 2024)
Introduction: Obesity and mild thyroid failure are common diseases, and the complex relationship between thyroid function and excess weight gain is still being researched. This study analyzes and summarizes the current scientific reports on the intricate correlation between thyroid dysfunction and obesity. Material and methods: We have gathered the available materials and scientific reports, analyzing and summarizing them in a single study. Aim of study: We aimed to summarize the studies conducted so far by analyzing the available scientific reports to answer the question of ‘what comes first’ and to understand the correlation between thyroid dysfunction and excessive weight gain. Discussion: Thyroid dysfunction in the form of hypothyroidism is associated with metabolic abnormalities, which may play a crucial role in the development of metabolic syndrome. On the other hand, excess level of leptin associated with excess adipose tissue is a potential cause of disruptions in the hypothalamic-pituitary-thyroid axis, manifested as elevated TSH levels. Therefore, it is worth considering certain aspects regarding the inclusion of hormone replacement therapy in obese patients presenting laboratory features of subclinical hypothyroidism. Conclusion. Obesity-induced thyroid dysfunction is typically reversible with weight loss and hormone replacement therapy should be considered for obese patients with subclinical hypothyroidism only if thyroid antibodies are present to confirm an autoimmune thyroid disorder.